2018
DOI: 10.1051/e3sconf/20183109007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Characteristics of Community-Based Tourism between Pentingsari and Nglanggeran Tourism Village, Special Region Yogyakarta

Abstract: Community-based tourism is one of the tourism development models that effectively used as a tool to alleviate poverty through empowerment strategy of the local community. Nevertheless, many people do not have adequate understanding on the characteristics of community-based tourism, which are used as a determinant in the tourism development. This article describes the comparison on characteristics of community-based tourism between Pentingsari and Nglanggeran. These villages were chosen because Pentingsari was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Bhalla and Bhattacharya (2019) stated that visitors' satisfaction as well as perception are the main elements that successfully drive the selection of destination, the consumption of the local products, and the generation of return visits in homestay tourism [26]. Purbasari and Manaf (2018) summarized the characteristic indicators of community-based tourism in Indonesia by comparative analysis, and the success dimensions for CBT from the evaluation research work include local community, good leadership, strong collaboration with government and private agencies, uniqueness of homestay attractions, and environmental conservation [27]. Kayat and Zainuddin (2016) listed 12 criteria of performance success of community-based rural homestays in rural Malaysia by a qualitative method [20].…”
Section: Success Factors Of Homestay Businessmentioning
confidence: 99%
“…Bhalla and Bhattacharya (2019) stated that visitors' satisfaction as well as perception are the main elements that successfully drive the selection of destination, the consumption of the local products, and the generation of return visits in homestay tourism [26]. Purbasari and Manaf (2018) summarized the characteristic indicators of community-based tourism in Indonesia by comparative analysis, and the success dimensions for CBT from the evaluation research work include local community, good leadership, strong collaboration with government and private agencies, uniqueness of homestay attractions, and environmental conservation [27]. Kayat and Zainuddin (2016) listed 12 criteria of performance success of community-based rural homestays in rural Malaysia by a qualitative method [20].…”
Section: Success Factors Of Homestay Businessmentioning
confidence: 99%
“…The government plays a role as a driver in the process of developing partnerships among stakeholders, developing and overseeing the strategic direction of tourist villages (Koopmans et al, (2018); Liu et al, (2020). To succeed, tourism villages require public partnerships both in the local and global contexts (Purbasari & Manaf, 2018). Research conducted by Kristianto et al (2019) found the critical success factors for developing a tourist village include attractions, facilities, accessibility, image, human resources, and tourism prices.…”
Section: Introductionmentioning
confidence: 99%
“…In its development, CBT requires public partnerships both in local and global contexts (Purbasari & Manaf, 2018). Regardless of the type of CBT services, these ventures should remain wholly owned, managed, and controlled by community members (or groups of independent micro and small experiences under the same CBT management organization).…”
Section: Introductionmentioning
confidence: 99%